Ti-MWW Catalysts for Propylene Oxide Production: Influence of Si/Ti Ratio and Calcination Conditions - Alvear Matias; Schmidt Christoph; Reinsdorf Ole; Lebron-Rodrigez Edgard; Al Abdulghani Abdullah; Hermans Ive; Peurla Markus; Lastusaari Mika; Eränen Kari; Murzin Dmitry Yu.; Kumar Narendra; Salmi Tapio (Springer, 2025)
Titanium silicates of MWW structures with different Si/Ti ratios were prepared via hydrothermal synthesis using piperidine as the structure directing agent and boric acid as the crystallization agent. All the syntheses resulted in highly crystalline materials independent of the Si/Ti ratio. The observed morphology showed MWW-like well-defined thin hexagonal platelets. The synthesized Ti-MWW materials exhibited higher surface areas and partial meso-porosity compared to the commercial TS-1 catalyst. The coordination of the Ti-species was investigated by UV–vis- and IR-spectroscopy. The MWW titanium silicates were tested for the catalytic performance in the epoxidation of propylene in a laboratory-scale trickle bed reactor to compare their clear different physico-chemical properties with the commercial TS-1. The synthesized Ti-MWW materials showed significantly higher catalytic activities, up to 3.5 times, using acetonitrile as the solvent and enhanced epoxide selectivities partially up to 100% in methanol unlike TS-1. The effect of the Ti content in the MWW and the calcination conditions were investigated in propylene epoxidation, revealing the beneficial effect of a lower calcination temperature and an increased Ti content on the activity. The catalytic results were correlated with the physico-chemical properties of the synthesized materials.